Evaluation of a new biomarker 14-3-3 Eta protein in diagnosis of rheumatoid arthritis - Lakshmi Deepika Yarlagadda; Rachel Jacob; D Liza Rajasekhar; Krishna Mohan Iyyapu; Sai Baba S S. Kompella; Vijaya Bhaskar Madrol; N N Sreedevi; Siraj Ahmed Khan; Noorjahan Mohammed (Indian Journal of Rheumatology)
Context: The lack of sensitivity and specificity of the existing diagnostic markers in Rheumatoid arthritis (RA) stimulates the search for new biomarkers to improve diagnostic sensitivity especially in seronegative cases. Aims: To estimate the levels of 14-3-3 η in RA cases, to assess the positivity of 14-3-3 η in seronegative RA and to correlate rheumatoid factor (RF) positivity with 14-3-3 η positivity in seropositive RA. Settings and Design: This was cross sectional case control study by the Departments of Biochemistry and Rheumatology and clinical immunology. Subjects and Methods: A total of 61 RA cases and 20 healthy controls were included. Erythrocyte sedimentation rate, high sensitivity C reactive protein, RF, anti-citrullinated peptide antibodies (CCP) and 14-3-3 η protein were estimated. RA cases were further classified as seropositive (n = 23) and seronegative (n = 38) based on the positivity of either RF or anti-CCP result. Statistical Analysis: Prism 7 (GraphPad Software Inc.). Results: The median levels of 14-3-3 η (ng/ml) in cases (0.66 [0.2–1.1]) were significantly high compared to controls (0.1 [0.07–0.28]), P < 0.0001. It had a sensitivity of 74% and specificity of 90% at >0.3 ng/ml. 14-3-3 η showed statistically significant difference between seronegative cases and controls (P = 0.0003). The sensitivity and specificity of RF and anti-CCP were 33% and 85% and 37% and 90% respectively. The combination of 14-3-3 η, RF and anti-CCP showed sensitivity and specificity of 85.4% and 100% respectively with area under the curve 0.927. Conclusions: Our study demonstrated that serum levels of 14-3-3 η were significantly higher in cases compared to controls. Seronegative RA cases showed 14-3-3 η positivity in 71% of cases. 14-3-3 η appears to be a useful and highly specific marker in RA.